2022
DOI: 10.3389/fonc.2022.945166
|View full text |Cite
|
Sign up to set email alerts
|

Positive surgical margins may not affect the survival of patients with renal cell carcinoma after partial nephrectomy: A meta-analysis based on 39 studies

Abstract: BackgroundSo far, whether positive surgical margin(PSM) has adverse effects on the prognosis of patients is still controversial, so we designed this study to systematically evaluate the effect of PSM on the prognosis of patients with renal cell carcinoma (RCC) after partial nephrectomy (PN).MethodsOn the basis of three electronic databases (PubMed, Embase and the Cochrane Library) up to May 2022, all case–control studies (CCSs) comparing the effects of PSM and negative surgical margin (NSM) after PN on the onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, the 5-year overall survival rates did not significantly differ between the two groups. This may suggest that while PSM is a strong predictor of recurrence, it may not independently predict overall survival, a phenomenon that has been observed in other studies [1,[14][15][16][17][18][19]. This could be attributed to the indolent nature of some RCC cases, where recurrence does not immediately translate to a survival disadvantage.…”
Section: Discussionmentioning
confidence: 82%
“…However, the 5-year overall survival rates did not significantly differ between the two groups. This may suggest that while PSM is a strong predictor of recurrence, it may not independently predict overall survival, a phenomenon that has been observed in other studies [1,[14][15][16][17][18][19]. This could be attributed to the indolent nature of some RCC cases, where recurrence does not immediately translate to a survival disadvantage.…”
Section: Discussionmentioning
confidence: 82%
“…However, in the present series, ccRCC variant histology and bilateral disease did not impact on OS probability upon univariable analysis ( p = 0.052 and p = 0.471, respectively). The positive surgical margin rate is considered an independent predictor of disease recurrence after nephron-sparing surgery for RCC ( p = 0.013) [ 32 ], while the impact of PSM on OS probabilities is negligible in the literature [ 33 ] as well as in the present study (univariable Cox p = 0.953). Concerning metastatic sites, Abdel-Rahman [ 34 ] evaluated the clinical and prognostic value of metastatic sites in mRCC; the author reported that patients with liver metastases of RCC have worse outcomes and worst OS compared to cases who developed other sites of metastases.…”
Section: Discussionmentioning
confidence: 96%